2019
DOI: 10.3390/catal10010016
|View full text |Cite
|
Sign up to set email alerts
|

Influences of MgO(001) and TiO2(101) Supports on the Structures and Properties of Au Nanoclusters

Abstract: Due to the unique structures, photoelectric properties, good catalytic activity, and broad potential applications, gold nanoclusters (Au n ) received extensive attention in catalysis, bioengineering, environmental engineering, and so on. In the present work, the structures and properties of Au n adsorbed on the MgO(001) and TiO 2 (101) surfaces were investigated by density functional theory. The results showed that the catalytic properties of Au n will be enhanced when Au n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
1
0
0
Order By: Relevance
“…43 There are even discrepancies in the global minimum structure prediction in the planar 2D regime for PBE, with some suggesting planar 2D structures that lie either perpendicular 37,43,44 or parallel to the surface. 19,41,45,46 By augmenting the PBE functional with the D3 dispersion correction, Engel et al 41 have actually found that planar parallel structures exist up until Au 19 �their largest studied nanocluster�and we show it extends up to Au 20 as well in this study. PBE-D3 is perhaps the most common DFT model used in surface chemistry, but alarmingly, these predictions by Engel et al 41 are in stark contrast to the 3D tetrahedral structure (see Figure 1) predicted by other studies 19,43,47 as well as strong experimental evidence.…”
Section: Introductionsupporting
confidence: 67%
“…43 There are even discrepancies in the global minimum structure prediction in the planar 2D regime for PBE, with some suggesting planar 2D structures that lie either perpendicular 37,43,44 or parallel to the surface. 19,41,45,46 By augmenting the PBE functional with the D3 dispersion correction, Engel et al 41 have actually found that planar parallel structures exist up until Au 19 �their largest studied nanocluster�and we show it extends up to Au 20 as well in this study. PBE-D3 is perhaps the most common DFT model used in surface chemistry, but alarmingly, these predictions by Engel et al 41 are in stark contrast to the 3D tetrahedral structure (see Figure 1) predicted by other studies 19,43,47 as well as strong experimental evidence.…”
Section: Introductionsupporting
confidence: 67%